FOSTERING CROSS-CULTURAL COMMUNICATION ETHICS THROUGH A MULTICULTURALISM PERSPECTIVE - Rahmat, Wahyudi; Septia, Emil; Tiawati, Refa Lina; Rahmad, Hari Adi (Bhandar: Harvesting Community Service in Asia, 2025)
This socialization initiative aims to enhance public understanding of the importance of cross-cultural communication ethics while fostering mutual respect through a multiculturalism approach. Recognizing the increasing intensity and complexity of intercultural interactions in the era of globalization, this program underscores the critical need for understanding cross-cultural communication to prevent misunderstandings and conflicts arising from cultural differences. The activities involve comprehensive discussions and interactive sessions that explore the principles of ethical communication, focusing on cultural sensitivity and respect. By employing the multiculturalism perspective, the initiative provides practical guidance for navigating cultural diversity effectively, promoting inclusivity and empathy in interpersonal and professional interactions. The program emphasizes the development of cultural competence as a foundation for building harmonious and respectful relationships among diverse communities. Through this socialization effort, we aspire to contribute positively to societal harmony and support individuals in embracing cultural diversity as a strength. This initiative seeks to prepare participants to engage in meaningful and respectful dialogue across cultural boundaries, ensuring smoother interactions in an increasingly interconnected world.